Geger Sikep: (Re) Interpretation of the Environment by Contemporary Movements in Kendeng, Central Java - Setiadi, Setiadi; Saraswati, Aprilia Rejeki; Rosyid, Nur (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2017)
For the last decade, the popularity and the imagery of Sedulur Sikep identity attribution on mass media rose and changed significantly, triggered by their involvement on a movement against cement factory plan in Kendeng, Central Java. Even so, some of the sikeps themselves claimed their absence and dissagrement on the movement. Thus, this anthropological study aims an explanation on how this situation led them to recognize the value of âbeing sikepâ and how it affected sikep or the âon behalf ofâ sikep movement in perceive and practice the conception of environment and its ecological issue. The paradigm shifting of ecology aspect on their cultural identity then tried to be mapped by looking on their ecological knowledge, the adaptability, and the power on controlling visibility space as a product of ânatureâ and ânurtureâ. Subsequently, it was found later that the disunity caused by their own personal experience on defining the reciprocity bond between their identity as peasant and the nature resources. The aftermath; dynamism and stagnancy then could be seen as their alter adaptation method, relying on how their belief conceive the ecological dispute and resistance towards the living space of Sedulur Sikep itself.